Malaysia MOOCs: students’ pattern of interaction - Mat Daud, Nuraihan; Abdul Latiff@Bapoo, Lili Suriani; Mat Daud, Nor Shidrah (2015)
Massive Open Online Courses (MOOC) provides an interactive avenue for unlimited number of participants to interact and collaborate on joint projects. Realising the potential of MOOCs in accommodating more and diverse learners, four MOOCs were introduced by the Malaysian Ministry of Education in 2014. These courses allowed students from all the Malaysian public educational institutions to benefit from the shared content. They were expected to discuss issues related to their field of studies and share their experiences. Postings sent were analysed to study their patterns of interaction particularly the number of postings, threads and patterns of turn-taking. The contents of the messages were also analysed to determine if they reflect effective learning. The study found that there was not much evidence of collaborative learning and co-construction of knowledge. There was a high percentage of greetings and sharing of ‘words of wisdom’ compared to discussions on issues related to the lessons. It was also observed that they wrote longer in the reflection page than in the discussion forum.